2018
DOI: 10.1016/j.concog.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

On a ‘failed’ attempt to manipulate visual metacognition with transcranial magnetic stimulation to prefrontal cortex

Abstract: Rounis, Maniscalco, Rothwell, Passingham, and Lau (2010) reported that stimulation of prefrontal cortex impairs visual metacognition. Bor, Schwartzman, Barrett, and Seth (2017) attempted to replicate this result, but adopted an experimental design that reduced their chanceof obtaining positive findings. Despite that, their results appeared initially consistent with those of Rounis et al., but they subsequently claimed it was necessary to discard ∼30% of their subjects, after which they reported a null result. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…Previous work demonstrated that lesions to prefrontal cortex affect metacognitive performance without altering first-order decision-making 67,68 . Similarly, disrupting prefrontal activity via theta burst stimulation has been shown to selectively alter metacognitive performance [69][70][71] (but see 72,73 ). The detection of erroneous behavior, a key aspect of metacognition 5,19 , has been strongly linked to a rapidly emerging central frontal negativity in the EEG signal (error-related negativity 74 ), thought to reflect coordinated theta oscillatory mechanisms [75][76][77][78][79] .…”
Section: Models Of Metacognitive Decision-makingmentioning
confidence: 99%
“…Previous work demonstrated that lesions to prefrontal cortex affect metacognitive performance without altering first-order decision-making 67,68 . Similarly, disrupting prefrontal activity via theta burst stimulation has been shown to selectively alter metacognitive performance [69][70][71] (but see 72,73 ). The detection of erroneous behavior, a key aspect of metacognition 5,19 , has been strongly linked to a rapidly emerging central frontal negativity in the EEG signal (error-related negativity 74 ), thought to reflect coordinated theta oscillatory mechanisms [75][76][77][78][79] .…”
Section: Models Of Metacognitive Decision-makingmentioning
confidence: 99%
“…Similarly, disrupting prefrontal activity via theta burst stimulation has been shown to selectively alter metacognitive performance (Rounis et al 2010;Ryals et al 2016;Shekhar and Rahnev 2018, but see Bor at al. 2017and Ruby et al 2018). The detection of erroneous behavior, a key aspect of metacognition (Yueng and Summerfield 2012;Fleming and Daw 2017), has been strongly linked to a rapidly emerging central frontal negativity in the EEG signal (error-related negativity, Falkenstein et al 1991), thought to reflect coordinated theta oscillatory mechanisms (Luu and Tucker 2001;Cohen et al 2008;Bates et al 2009;Cavenagh et al 2009;Cohen and Cavenagh 2011).…”
Section: Prefrontal Cortex and Metacognitionmentioning
confidence: 99%
“…The use of different hands for these different responses would more definitively rule out contributions from these types of response biases. Finally, in the current study, hit rates were relatively high for some participants, creating potentially unstable estimates of second-order performance (Bor et al, 2017;Ruby et al, 2018). A staircase procedure before the experiment could address this issue in future studies.…”
Section: Limitationsmentioning
confidence: 79%